2020
DOI: 10.1016/j.neuron.2020.05.036
|View full text |Cite
|
Sign up to set email alerts
|

SNAREopathies: Diversity in Mechanisms and Symptoms

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 137 publications
9
111
0
Order By: Relevance
“…Our results are in agreement with recent in vitro studies showing that DAP also can overcome release deficits associated with disease‐causing synaptotagmin‐1 variants (Bradberry et al, 2020). Taken together, these observations confirm and expand our hypothesis that augmentation of release by DAP or 4‐AP would be a viable treatment option for other SNAREopathies as well (Baker et al, 2018; Harper, Mancini, van Slegtenhorst, & Cousin, 2017; Salpietro et al, 2017; Verhage & Sorensen, 2020). This approach could be tested in vitro before clinical implementation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are in agreement with recent in vitro studies showing that DAP also can overcome release deficits associated with disease‐causing synaptotagmin‐1 variants (Bradberry et al, 2020). Taken together, these observations confirm and expand our hypothesis that augmentation of release by DAP or 4‐AP would be a viable treatment option for other SNAREopathies as well (Baker et al, 2018; Harper, Mancini, van Slegtenhorst, & Cousin, 2017; Salpietro et al, 2017; Verhage & Sorensen, 2020). This approach could be tested in vitro before clinical implementation.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together, these observations confirm and expand our hypothesis that augmentation of release by DAP or 4-AP would be a viable treatment option for other SNAREopathies as well (Baker et al, 2018;Harper, Mancini, van Slegtenhorst, & Cousin, 2017;Salpietro et al, 2017;Verhage & Sorensen, 2020). This approach could be tested in vitro before clinical implementation.…”
Section: Discussionsupporting
confidence: 80%
“…The synaptic exocytic SNAREs have known roles in key processes of neural development, such as axon guidance (Barrecheguren et al, 2017; Cotrufo et al, 2011; Ros et al, 2018). Unsurprisingly, therefore, genetic mutations or variants of these SNAREs and their interacting partners of the synaptic exocytic machinery, particularly, give rise to an array of neurological manifestations in humans and mice (Cupertino et al, 2016; Verhage & Sørensen, 2020). These are broadly summarized in Table 1, and shall be considered below.…”
Section: Neurodevelopmental Disorders Associated With the Canonical Smentioning
confidence: 99%
“…Neurological disorders, or SNAREopathies (Verhage & Sørensen, 2020), that are associated with MUNC18‐1 have in fact been much more widely identified compared to its SNARE partners. Early analysis the Drosophila MUNC18‐1 orthologue Rop showed that null mutants die at a late embryonic stage (Harrison et al, 1994) and various Rop mutation affect neurotransmission (M. N. Wu et al, 1998).…”
Section: Neurodevelopmental Disorders Associated With the Canonical Smentioning
confidence: 99%
“…SNARE proteins are generally small proteins of around 100–300 aminoacids and they mediate the fusion of biological membranes by localizing both at the vesicular membrane and on the target membrane (for further details please refer to [ 23 , 24 , 25 , 26 , 27 ]. They share a common domain, the SNARE motif, which is normally of 60 aa in length.…”
Section: Introductionmentioning
confidence: 99%